2015
DOI: 10.1177/1756283x15622600
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplant for Clostridium difficile infection in older adults

Abstract: FMT is a generally safe and effective treatment option for older adults with CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…[14][15][16][17][18] Figure 1 shows the flow diagram of study selection. Fifteen studies, published between 2012 and 2017, were included for the final analysis, 4,11,[19][20][21][22][23][24][25][26][27][28][29][30][31] including two RCTs, 4,11 nine retrospective case series [19][20][21][22][24][25][26][27]29 and four prospective case series. 23,28,30,31 Most were single-centre studies and three were multicentre studies.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…[14][15][16][17][18] Figure 1 shows the flow diagram of study selection. Fifteen studies, published between 2012 and 2017, were included for the final analysis, 4,11,[19][20][21][22][23][24][25][26][27][28][29][30][31] including two RCTs, 4,11 nine retrospective case series [19][20][21][22][24][25][26][27]29 and four prospective case series. 23,28,30,31 Most were single-centre studies and three were multicentre studies.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…[ 26 ] The risk of CDI is greater if the prevalence of CDI at the hospital is high during an admission, a concept known as “colonization pressure.”[ 27 ] Inflammatory bowel disease, chemotherapy, ongoing malignancy, chronic kidney and liver disease, pregnancy, HIV infection, chronic corticosteroid treatment, and gastrointestinal (GI) surgery or manipulation (including feeding tubes) are additional risk factors. [ 6 11 12 28 29 30 31 ] The recent increase in the incidence of CDI may be due to demographic changes among admitted patients, including older age, multi-morbidity, polypharmacy, as well as the emergence of the BI/NAP/027 strain. [ 6 32 ] Recurrent CDI (RCDI) has been associated with continued use of antibiotics, severe initial CDI, older age, multiple comorbidities, and gastric acid suppression therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A small case review study of 31 patients aged 65 years or older showed CDI revolved in 27/31 patients. In this analysis, five deaths occurred in follow-up, although the FMT was not thought to be a causative factor in these cases, and four patients reported subjective worsening of their arthritis post-FMT leading the study to conclude that FMT is generally a safe and effective treatment even in older adults with CDI [74].…”
Section: Safety Of Fmtmentioning
confidence: 80%